Evaluation of SICAN performance for biofouling mitigation in the food industry. (April 2016) - Moreira, J.M.R.; Fulgêncio, R.; Alves, P.; Machado, I.; Bialuch, I.; Melo, L.F.; Simões, M.; Mergulhão, F.J.
Abstract: Biological fouling in food industry leads to an increase in maintenance costs, decreases operational efficiencies and promotes food contamination leading to economic losses and the dissemination of foodborne pathogens. In order to maintain production efficiency and hygienic standards, cleaning in place (CIP) procedures are required. However, the existence of critical zones shielded from the main flow carrying the CIP disinfectants requires new strategies for reducing biofilm buildup and/or easy to clean surfaces. In this work, a Diamond-Like Carbon (DLC) coating modified by incorporation of silicon (a-C:H:Si or SICAN), was evaluated regarding bacterial adhesion, biofilm formation and cleanability. Assays included the natural flora present in industrial water (from a salad washing line) and Escherichia coli, one of the most persistent foodborne microorganisms. Results show that bacterial adhesion and biofilm formation on SICAN and stainless steel were similar, thus surface modification was not able to prevent biological fouling development. However, it was verified that after performing a cleaning protocol with chlorine, reduction of bacterial counts was much higher in SICAN (about 3.3 Log reduction) when compared to stainless steel (1.7 Log reduction). Although full biofilm recovery was observed on both surfaces 18 h after treatment, an operational window was identified for which processes with cleaning intervals of about 6 h could potentially use SICAN surfaces on critical areas (such as dead zones, crevices, corners, joints) and therefore operate at a much higher hygienic level than the one attained with stainless steel. Highlights: The use of SICAN does not decrease short-term bacterial adhesion. Escherichia coli and the flora from industrial water had similar adhesion behaviour. The use of SICAN can be beneficial for industries with frequent cleaning duties. For industries with longer cleaning intervals SICAN may not be a good option.